Odpowiedzi

Najlepsza Odpowiedź!
2010-03-11T20:00:48+01:00
A) 3 - y < 5 + y - 2y
-y - y + 2y < 5 - 3
0 < 2
zawsze prawdziwe
Z = R

b) 5(2x+3) > 2(x-3)+x
10x + 15 > 2x - 6 + x
10x - 2x - x > -6 - 15
7x > -21 /:7
x > -3
Z = (-3; +nieskończoność)

c) -3(z-2)-2 < z-5-4z
-3z + 6 - 2 < z - 5 - 4z
-3z - z + 4z < -5 - 6 + 2
0 < -9
nierówność sprzeczna
Z = Ф

d) 7y-25(y-4) > 6-(2-y)
7y - 25y + 100 > 6 - 2 + y
7y - 25y - y > 6 - 2 - 100
-19y > -96 /:(-19)
y < 5 ¹/₁₉
Z = (-nieskończoność ; 5 ¹/₁₉)

e) 4(2-x)-3(1-x) < 5(1-x)
8 - 4x - 3 + 3x < 5 - 5x
-4x + 3x + 5x < 5 + 3 - 8
4x < 0 /:4
x < 0
Z = (-nieskończoność ; 0)

f) -2/3y-(2-3y) < 5y+2(1-y)
-2/3y - 2 + 3y < 5y + 2 - 2y
-2/3y + 3y - 5y + 2y < 2 + 2
-2/3y < 4 / ×(-3/2)
y > -6
Z = (-6; +nieskończoność)